2018
DOI: 10.3748/wjg.v24.i44.4979
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione depleting drugs, antioxidants and intestinal calcium absorption

Abstract: Glutathione (GSH) is a tripeptide that constitutes one of the main intracellular reducing compounds. The normal content of GSH in the intestine is essential to optimize the intestinal Ca2+ absorption. The use of GSH depleting drugs such as DL-buthionine-S,R-sulfoximine, menadione or vitamin K3, sodium deoxycholate or diets enriched in fructose, which induce several features of the metabolic syndrome, produce inhibition of the intestinal Ca2+ absorption. The GSH depleting drugs switch the redox state towards an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 92 publications
2
13
0
Order By: Relevance
“…Glutathione peroxidase (GSH-Px) is involved in converting between reduced glutathione and oxidized glutathiol, reduced H 2 O 2 to H 2 O, and lipid peroxides to alcohols. Total antioxidant capacity (T-AOC) was used as an indicator of the overall antioxidant capacity of the organism ( 47 , 48 ). In our research, diets with HMOA supplementation enhanced the content of SOD and CAT in the serum of 21 and 42 d-broiler, respectively, and the level of T-AOC, SOD, and CAT were increased in serum of 42 d-broiler fed with LMOA.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione peroxidase (GSH-Px) is involved in converting between reduced glutathione and oxidized glutathiol, reduced H 2 O 2 to H 2 O, and lipid peroxides to alcohols. Total antioxidant capacity (T-AOC) was used as an indicator of the overall antioxidant capacity of the organism ( 47 , 48 ). In our research, diets with HMOA supplementation enhanced the content of SOD and CAT in the serum of 21 and 42 d-broiler, respectively, and the level of T-AOC, SOD, and CAT were increased in serum of 42 d-broiler fed with LMOA.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal tract is the primary organ controlling these processes. The duodenum-the first digestive and absorptive organ of the intestinal tract-is vital for the absorption of glucose (Zhong et al, 2020), fat (Everard et al, 2019), vitamin B (Wang et al, 2019), calcium (Moine, 2018), zinc (Zhong et al, 2020), and iron (Andrews, 2008). Therefore, to better understand how the duodenum and its functions are associated with RFI phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…As previous reports shown, quercetin is a flavonoid aglycone that has 3-OH groups and inhibits the formation of chain oxidation and terminates chain propagation in ROS production [ 51 ]. GSH-related redox homeostasis regulated by Nrf2 signaling is also an important contributes against oxidative injury in enterocytes [ 52 ]. As previous study shown, diquat was found to increase the oxidized glutathione (GSSG) content, decrease the GSH content, and increased the ratio of GSSG/GSH in the intestine of piglets [ 39 ], and similar results were also observed in our in vitro studies.…”
Section: Discussionmentioning
confidence: 99%